Design and analysis of square shaped serrated patch antenna for ultra-wideband applications with single rejection band - Saleem Akram, P; T P Madhav, B; Jeevana Sravya, G; Sudhakar, V; Lakshmi Sirisha, G; Mounika, Ch; Venkateswara Rao, M (International Journal of Engineering and Technology, 2017)
This article studies about the design and analysis of serrated patch antenna with a slot at the ground with microstrip line feed. Comparative analysis has been carried in five and ten serrated patches at top and side edges of the square patch. All design iterations have been carried out using commercially equipped tool HFSS 13. For bandwidth enhancement a slot has been placed at the ground in all iterations in common, later the return loss and gain have been analyzed and compared for all models. Finally, the proposed modal consists of ten serrations at the three edges of the square patch where it works on the ultrawide band region with high gain when compared to all models. The proposed antenna has its applications at WiMAX, WLAN 802.11, LTE 42/43 bands and works in the region of ultrawide band(3.1GHz-10.6GHz).and having rejection at 5-6GHz